Pengaruh Kepercayaan dan Electronic Word of Mouth terhadap Keputusan Menginap di Daima Hotel Padang (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This research is motivated by the phenomenon in the decision-making process for overnight stays, which is suspected to be influenced by trust and E-WOM found on the internet. This research was conducted to identify and analyze the influence of Trust and E-WOM on guests' decisions to choose to stay at Daima Hotel Padang. The research population includes guests who have stayed at the hotel during the period from January to March 2025, with a sample size of 130 people obtained through non-probability sampling techniques. Data collection was conducted through questionnaires, observations, interviews, and literature studies. The partial analysis results show that the Trust variable has a significant influence on the decision to stay, as evidenced by a significance value of 0.137, which is less than 0.05 (0.137 < 0.05). Meanwhile, the testing of the E-WOM variable also shows a significant influence on the decision to stay, with a significance value of 0.005, which is also less than 0.05 (0.005 < 0.05).